Gardens of Renaissance Europe and the Islamic Empires : Encounters and Confluences - Gharipour, Mohammad (Book collections on Project MUSE., 2017)
"A collection of essays exploring similarities between gardens and designed landscapes in Europe and the Islamic world after the fifteenth century. Essays identify possible direct or indirect influences and examine transcontinental mutual influences in garden design"--Provided by publisher